In support of market-driven standards - Matthias Bauer; Fredrik Erixon; Oscar Guinea; Vanika Sharma (European Centre for International Political Economy (ECIPE), 2023)
The EU published its new Standardisation Strategy in 2022. The strategy contains some good ideas to improve the way European standards are set. However, in its attempt to gain more control over technical standards, the EU risks killing the goose that lays the golden egg. The primary motivation behind the strategy is the belief that the process governing the way CEN, CENELEC, and ETSI - the three European Standardisation Organisations - take decisions over EU standards favours non-EU multinationals. To address this perceived imbalance, EU National Standardisation Bodies will have the exclusive power to accept standardisation requests, and adopt, revise and withdraw European technical standards. These changes are particularly significant for ETSI, Europe's Standardisation Body in charge of telecommunication standards and one of Europe's most successful organisations. ETSI is a prime example of EU normative power since it hosts companies from more than 60 countries, while retaining a large membership of EU firms.
Keywords: 330; Standardization; EU research policy; Information technology; Standardisierung; EU-Forschungspolitik; Informationstechnik